PSXI-41 Effect of different homoserine lactones on in vitro rumen fermentation. (7th December 2018) - Kim, Y; Jeon, E; Ryu, C; Oh, S; Lee, J; Cho, S; Choi, N
Abstract: Bacteria use a mechanism of cell-cell communication for various metabolic and ecological strategies, and this mechanism is known as quorum signaling (QS). This system is achieved by many different types of autoinducers of which acy homoserine lactones (AHLs) are examples. Although QS has been observed in the rumen, its role in rumen microbial ecosystem has not yet been described in detail. This study was aimed to investigate how rumen fermentation profiles could be altered by infusion of different AHLs. Rumen content collected from two cannulated Holstein cows was mixed with McDougal solution (1:4) and then used as rumen inoculum. A total mixed ration diet (Nutrients %DM: CP, 16; NDF, 31; EE, 3; Ash, 5; NFE, 43; Starch, 40) was used as basal diet. Finely ground 1 g of basal diet was mixed with 50 mL of rumen inoculum before 50 nM of 5 different AHLs (HSL1, N-(3-Hydroxydodecanoyl)-DL-homoserine lactone; HSL2, N-(3-Hydroxytetradecanoyl)-DL-homoserine lactone; HSL3, N-Dodecanoyl-DL-homoserine lactone; HSL4, N-(p-Coumaroyl)-L-homoserine lactone; HSL5, N-(3-Oxooctanoyl)-L-homoserine lactone) were infused, with methanol included as the control. HSL2 and HSL3 showed significantly low ammonia nitrogen compared to others (p<0.05). Gas production and total volatile fatty acids production were not influenced by AHLs. However, acetate, butyrate and valerate production were significantly altered (p<0.05). HSL3 showed the greatest acetate, butyrate and valerate production (p<0.05). These results indicated a possible modification of rumen fermentation by homoserine lactones, an autoinducer of bacterial communication system.